The growing importance of food and culinary knowledge and skills in dietetics practice - Canter, Deborah D.; Moorachian, Mary Etta; Boyce, Janice (My University, 2008)
Do food and nutrition professionals have adequate competence in the food and culinary sciences to comfortably and confidently translate clinical recommendations into practical applications? Knowledge of food is critical for most areas of dietetics practice. Whether in clinical, community, foodservice, or more nontraditional settings, the registered dietitian that is competent in speaking food and culinary language is more effective in enabling consumers to make the food-health connection. A major challenge facing many dietetic education programs today is outdated and poorly equipped facilities for teaching foods classes. Another problem centers on faculty teaching foods classes may have minimal nutrition education and training, and thus may find teaching food preparation in a "healthy" context a challenge. Other challenges include curriculum restrictions and lack of prerequisite knowledge on the part of students about foods and cooking. These issues must be faced if dietetics educators are to prepare future dietetics professionals as the true food and nutrition experts.
Keywords: Culinary; Food; Dietetics; Registered dietitians